Stratum corneum occlusion induces water transformation towards lower bonding state: a molecular level in vivo study by confocal Raman microspectroscopy. (26th August 2020) - Choe, C.; Schleusener, J.; Choe, S.; Ri, J.; Lademann, J.; Darvin, M. E.
Abstract: Objective: It is conventionally understood that occlusive effects are the retention of excessive water in the stratum corneum (SC), the increase of SC thickness (swelling) and a decrease of the transepidermal water loss. However, the influence of occlusion on water binding properties in the SC is unknown. Methods: The action of plant‐derived jojoba and almond oils, as well as mineral‐derived paraffin oil and petrolatum topically applied on human skin, is investigated in vivo using confocal Raman microspectroscopy. To understand the oils' influence on the SC on the molecular level, the depth‐dependent hydrogen bonding states of water in the SC and their relationship to the conformation of keratin, concentration of natural moisturizing factor (NMF) molecules and lipid organization were investigated. Results: A significant SC swelling was observed only in petrolatum‐treated skin. The water concentration was increased in oil‐treated skin in the intermediate SC region (40–70% SC depth). Meanwhile, the amount of free, weakly and tightly bound water increased, and strongly bound water decreased in the uppermost SC region (0–30% SC depth). The NMF concentration of oil‐treated skin was significantly lower at 50–70% SC depth. The lateral organization of lipids in oil‐treated skin was lower at 0–30% SC depth. The secondary structure of keratin was changed towards an increase of β ‐sheet content in mineral‐derived oil‐treated skin and changed towards an increase of α ‐helix content in plant‐derived oil‐treated skin. Conclusion: The occlusive properties can be summarized as the increase of free water and the transformation of water from a more strongly to a more weakly hydrogen bonding state in the uppermost SC, although some oils cause insignificant changes of the SC thickness. The accompanied changes in the keratin conformation at the intermediate swelling region of the SC also emphasize the role of keratin in the SC's water‐transporting system, that is the water in the SC transports intercellularly and intracellularly in the intermediate swelling region and only intercellularly in the uppermost non‐swelling region. Bearing this in mind, almond, jojoba and paraffin oils, which are not occlusive from the conventional viewpoint, have an occlusion effect similar to petrolatum on the SC. Abstract : The occlusive properties of the SC can be summarized as the increase of free water and the transformation of water from a more strongly to a more weakly hydrogen bonding state in the uppermost SC. The accompanied changes in the keratin conformation at the intermediate swelling region of the SC also emphasize the role of keratin in the SC's water‐transporting system, that is the water in the SC transports intercellularly and intracellularly in the intermediate swelling SC region and only intercellularly in the uppermost non‐swelling SC region. Bearing this in mind, almond, jojoba and paraffin oils, which are not occlusive from the conventional viewpoint, have an occlusion effect similar to petrolatum on the SC. Résumé: Objectif: Il est généralement entendu que les effets occlusifs consistent en la rétention d'un excès d'eau dans la couche cornée (stratum corneum, SC), l'augmentation d'épaisseur de la SC (gonflement) et une diminution de la perte d'eau trans‐épidermique. Cependant, l'influence de l'occlusion sur les propriétés de fixation de l'eau dans le SC est inconnue. Méthodes: L'action des huiles de jojoba et d'amande d'origine végétale, ainsi que des huiles de paraffine et de pétrolatum d'origine minérale appliquées topiquement sur la peau humaine est étudiée in vivo à l'aide de la microspectroscopie Raman confocale. Pour comprendre l'influence des huiles sur le SC au niveau moléculaire, on a étudié les états de liaison hydrogène de l'eau dans le SC en fonction de la profondeur et leur relation avec la conformation de la kératine, la concentration des molécules du facteur naturel d'hydratation (NMF) et l'organisation des lipides. Résultats: Un gonflement significatif de le SC n'a été observé que dans la peau traitée au pétrolatum. La concentration en eau a été augmentée dans la peau traitée au pétrolatum dans la région SC intermédiaire (40‐70% de profondeur du SC). En meme temps, la quantité d'eau libre, faiblement et fortement liée augmentait, tandis que l'eau fortement liée diminuait dans la région SC supérieure (0‐30% de profondeur du SC). La concentration en NMF de la peau traitée à l'huile était plus basse d´une manière significative à 50‐70% de profondeur du SC. L'organisation latérale des lipides dans la peau huilée était plus basse à une profondeur du SC de 0 à 30 %. La structure secondaire de la kératine a été modifiée pour augmenter la teneur en feuillet‐β dans les peaux huilées d'origine minérale et pour augmenter la teneur en hélice α dans les peaux huilées d'origine végétale. Conclusion: Les propriétés occlusives peuvent être résumées comme l'augmentation de l'eau libre et la transformation de l'eau d'un état de liaison hydrogène plus fort à un état de liaison hydrogène plus faible dans le SC supérieure, bien que certaines huiles provoquent des changements insignifiants de l'épaisseur de la SC. Les modifications de la conformation de la kératine dans la zone de gonflement intermédiaire du SC soulignent également le rôle de la kératine dans le système de transport de l'eau du SC, c'est‐à‐dire que l'eau est transportée du SC de manière intercellulaire et intracellulaire dans la zone de gonflement intermédiaire et seulement de manière intercellulaire dans la zone non gonflée la plus élevée. En considérant cela, les huiles d'amande, de jojoba et de paraffine, qui ne sont pas occlusives du point de vue conventionnel, ont un effet d'occlusion similaire à celui du pétrolatum sur le SC.